Pendampingan Masyarakat dalam Pengembangan BUMMA (Badan Usaha Milik Madrasah) MA Raudlatul Ulum Putri Ganjaran - Fatkhul Wahab (Jurnal Aksi Afirmasi, 2023)
Assistance for improving Madrasah-Owned Enterprises (BUMMA) MA Radlatul Ulum Putri is one of the efforts that must be made to improve and optimize the resources owned by MA Raudlatul Ulum Putri including its human resources with the existence of activities to improve the quality of human resources and resources in MA Raudlatul Ulum Putri at least rising the motivation in the school of Raudlatul Ulum Putri is getting better as expected. With this good chance, it will give confidence to the community and comfort for students in meeting their needs so that they can study well and calmly.